Herpes Mastitis: Diagnosis and Management. Issue 3 (21st February 2016) - Toussaint, Arnaud; Simonson, Colin; Valla, Christian
Abstract: Herpetic lesions most frequently occur on oral and genital areas. However, herpes simplex virus (HSV) can be a rare cause of breast infection. In few published articles, the route of transmission is predominantly from infant to mother. We report two cases about simultaneous mammary and extramammary (oral and genital) herpetic infection in nonlactating women. In both cases, HSV breast lesions were acquired by sexual contacts with partners who were asymptomatic HSV carriers. Through a review of literature, we highlight clinical signs for an early diagnosis. We also emphasize the advantage of the valacyclovir for treating this uncommon pathology.